Proteomic analysis reveals dynamic changes in cloacal fluid composition during the reproductive season in a sexually promiscuous passerine - Míčková, Kristýna; Jelínek, Václav; Tomášek, Oldřich; Stopková, Romana; Stopka, Pavel; Albrecht, Tomáš (Scientific reports, 2024)
Cryptic female choice (CFC) is a component of postcopulatory sexual selection that allows females to influence the fertilization success of sperm from different males. While its precise mechanisms remain unclear, they may involve the influence of the protein composition of the female reproductive fluids on sperm functionality. This study maps the protein composition of the cloacal fluid across different phases of female reproductive cycle in a sexually promiscuous passerine, the barn swallow. Similar to mammals, the protein composition in the female reproductive tract differed between receptive (when females copulate) and nonreceptive phases. With the change in the protein background, the enriched gene ontology terms also shifted. Within the receptive phase, distinctions were observed between proteomes sampled just before and during egg laying. However, three proteins exhibited increased abundance during the entire receptive phase compared to nonreceptive phases. These proteins are candidates in cryptic female choice, as all of them can influence the functionality of sperm or sperm-egg interaction. Our study demonstrates dynamic changes in the cloacal environment throughout the avian breeding cycle, emphasizing the importance of considering these fluctuations in studies of cryptic female choice.
Keywords: Seasons; Reproduction; proteomika; sexuální chování zvířat; mužské pohlaví; Cloaca; Proteomics; ženské pohlaví; kloaka; Proteome; zvířata; Passeriformes; rozmnožování; proteom; Female; Sexual Behavior, Animal; Spermatozoa; roční období; spermie; Male; Animals